A validated photonumeric scale for infraorbital dark circles and its application in evaluating the efficacy of a cosmetic treatment product in a split‐face randomized clinical trial. (18th December 2020) - O'Mahony, M.M.; Sladen, C.; Crone, M.; Banner, E.; Newton, V.L.; Allen, A.; Bell, M.; Marlow, I.; Acevedo, S.F.; Jiang, L.I.
Abstract: Objective: As a result of their complex aetiology and periodicity, dark circles are difficult to characterize and measure, with current assessment techniques relying on specialist equipment, image analysis or proprietary grading scales. There is therefore a need to develop and validate a photonumeric scale for assessing infraorbital dark circles, which can provide an objective and consumer relevant tool for evaluating this condition and the efficacy of treatment products and procedures. Methods: A panel of expert clinical evaluators reviewed approximately three thousand facial photographs collected over a 5‐year period and selected images representing a dynamic range of dark circles. A 10‐point photonumeric scale was created, with corresponding descriptors and images for each grade of the scale. To rigorously validate the scale, linearity, sensitivity and precision were assessed by colorimetry and in‐clinic evaluation. Reproducibility was assessed photographically with both experienced and inexperienced clinical evaluators, whereas intragrader repeatability was assessed live in‐clinic. The scale was then employed in a split‐face randomized clinical trial on 58 subjects to evaluate the efficacy of a cosmetic treatment product over 8 weeks. Results: Colour analysis of the images showed the scale was linear, with statistically significant correlations observed when colour data (CIElab; Individual Typology Angle) were plotted against the corresponding grades ( r  > 0.9, P  < 0.001). Colour difference (Delta E) was calculated between the infraorbital zone and the surrounding skin, and when data were plotted against the grades, a statistically significant correlation was observed ( r  = 0.99, P  < 0.01). The magnitude of the Delta E suggested that changes in grade are visibly perceptible to the human eye, and therefore, the scale is sensitive and clinically relevant. Intergrader reproducibility showed strong correlation (0.96) and >90% agreement between experienced evaluators, whereas intragrader repeatability assessment showed >90% perfect agreement between grades. Use of this scale in a clinical trial demonstrated the efficacy of a cosmetic product, with a mean statistically significant ( P  < 0.001) decrease in grade of 0.74 compared to baseline, and 0.59 versus the untreated control, after 8 weeks of treatment. Conclusion: Our photonumeric scale for infraorbital dark circles is sensitive and robust and provides an objective and easy‐to‐use tool to evaluate dark circles and their treatment. Abstract : A 10‐point photonumeric scale was created, with corresponding descriptors and images for each grade of the scale. The scale has been rigorously validated and used in a split‐face randomised clinical trial to evaluate the efficacy of a cosmetic treatment product over 8 weeks. Résumé: Objectif: En raison de leur étiologie et de leur périodicité complexes, les cernes sont difficiles à caractériser et à mesurer, les techniques d'évaluation actuelles reposant sur des équipements spécialisés, l'analyse d'images ou des échelles de notation exclusives. Il est donc nécessaire de développer et de valider une échelle photonumérique pour évaluer les cernes infraorbitaires, laquelle peut fournir un outil objectif et pertinent pour le consommateur et tester l'efficacité des produits et des procédures de traitement. Méthodes: Un panel d'évaluateurs cliniques experts a examiné environ trois mille photographies du visage recueillies sur une période de 5 ans, ainsi que des images sélectionnées représentant une plage dynamique de cernes. Une échelle photonumérique à 10 points a été créée, avec des descripteurs et des images correspondants à chaque grade de l'échelle. Afin de valider rigoureusement l'échelle, la linéarité, la sensibilité et la précision ont été évaluées par colorimétrie et en clinique. La reproductibilité a été évaluée sur le plan photographique par des évaluateurs cliniques expérimentés et inexpérimentés, tandis que la répétabilité intragrade a été évaluée en direct en clinique. L'échelle a ensuite été utilisée dans un essai clinique randomisé à deux parties sur 58 sujets, afin d'évaluer l'efficacité d'un produit de traitement cosmétique sur 8 semaines. Résultats: L'analyse des couleurs des images a montré que l'échelle était linéaire, avec des corrélations statistiquement significatives observées lorsque les données de couleurs (CIElab ; angle de typologie individuel) ont été tracées par rapport aux grades correspondants (r > 0, 9, P < 0, 001). La différence de couleur (Delta E) a été calculée entre la zone infraorbitaire et la peau environnante, et lorsque les données ont été tracées par rapport aux grades, une corrélation statistiquement significative a été observée (r = 0, 99, P < 0, 01). L'ampleur du delta E a suggéré que les changements de grade sont visiblement perceptibles à l'œil humain, l'échelle étant par conséquent sensible et cliniquement pertinente. La reproductibilité intergrade a montré une forte corrélation (0, 96) et une concordance > 90 % entre les évaluateurs expérimentés, tandis que l'évaluation de la répétabilité intragrade a montré une concordance parfaite > 90 % entre les grades. L'utilisation de cette échelle lors d'un essai clinique a démontré l'efficacité d'un produit cosmétique, avec une diminution moyenne statistiquement significative (P < 0, 001) du grade de 0, 74 par rapport à la référence, et de 0, 59 par rapport au témoin non traité, après 8 semaines de traitement. Conclusion: Notre échelle photonumérique pour les cernes infraorbitaires est sensible et robuste, fournissant un outil objectif et facile à utiliser afin d'évaluer les cernes et leur traitement.